1999
DOI: 10.3171/foc.1999.7.1.2
|View full text |Cite
|
Sign up to set email alerts
|

Predicting the probability of meningioma recurrence based on the quantity of peritumoral brain edema on computerized tomography scanning

Abstract: Object The goal of this study was to determine whether the quantity of peritumoral brain edema displayed on computerized tomography (CT) scanning could be correlated with brain invasion and subsequent recurrence of meningiomas. Methods One hundred thirty-five patients who underwent resection of intracranial meningiomas at the Ottawa Civic Hospital were followed during the period 1980 to 1998. A complete … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
31
0
4

Year Published

2000
2000
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(38 citation statements)
references
References 34 publications
(41 reference statements)
3
31
0
4
Order By: Relevance
“…Of the 83 patients in the study, a 5-year recurrence rate for benign meningiomas was 3.1%, but 45.5% and 85.7% 5-year recurrence rates were seen following a typical and malignant meningiomas, respectively. The recurrence rate rise with the histological grade rising, consistent with the findings of Ayerbe [6] et al Mantle et al [1] reported the meningiomas' cell would invade brain tissue along cell, forming bridges between cortex and surface of tumor, so they thought the invasive cell was the main reason for tumor recurrence. We suggested, for the typical and malignant meningiomas, Simpson Grade 0 or Grade I resection should be taken, if it is possible, and adjuvant radiation therapy is necessary.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…Of the 83 patients in the study, a 5-year recurrence rate for benign meningiomas was 3.1%, but 45.5% and 85.7% 5-year recurrence rates were seen following a typical and malignant meningiomas, respectively. The recurrence rate rise with the histological grade rising, consistent with the findings of Ayerbe [6] et al Mantle et al [1] reported the meningiomas' cell would invade brain tissue along cell, forming bridges between cortex and surface of tumor, so they thought the invasive cell was the main reason for tumor recurrence. We suggested, for the typical and malignant meningiomas, Simpson Grade 0 or Grade I resection should be taken, if it is possible, and adjuvant radiation therapy is necessary.…”
Section: Discussionsupporting
confidence: 79%
“…Knowing extent of resection affects recurrence, some neurosurgeons mention Simpson Grade 0 resection. Simpson Grade 0, which means gross total resection of tumor, abnormal bone, and dural located within 2 cm of the bound of meningiomas [1,2] . But the Simpson Grade 0 resection is limited to cerebral convexity meningiomas, for it is hard to do it because of meningiomas' location.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, paradoxically, benign meningiomas, which typically have a broad base of attachment to the dura mater, frequently indent and occasionally invade into the brain. 30 Because these invasive cells contribute to the failure of complete tumor resection, 6,30 studies aimed at the elucidation of the molecular mechanisms that regulate the invasion process in meningiomas are highly imperative. Tumor cell invasion is a complex multistep process that involves cell attachment, the proteolysis of extracellular matrix, and cellular migration.…”
Section: Table 3 Correlation Between the Ets-1 And U-pa Expression Inmentioning
confidence: 99%
“…Indistinct borders, mushroomlike projections from the tumor, invasion deep into the brain, patchy enhancement, absence of calcification, necrosis, and marked edema may favor a diagnosis of malignant meningioma but neither CT nor MRI is diagnostic. 22,27,[32][33][34][35] The Histopathological Classification of Meningiomas has been Evolving Since 1938…”
Section: Mri and Ct Have Complementary Roles In Diagnosismentioning
confidence: 99%